Manajemen Manajemen Risiko Pembiayaan Bermasalah (NPF) pada BPRS Indonesia: Pendekatan Fiqih dan Regulasi - Bunga Aulia Khafifa; Joko Setyono; Rafidah Rizky Nasution (MAMEN: Jurnal Manajemen, 2026)
This study aims to analyze Non-Performing Financing (NPF) risk management in Sharia Rural Banks (BPRS) in Indonesia from the perspectives of fiqh muamalah (Islamic commercial jurisprudence) and regulatory frameworks. A qualitative approach was employed, utilizing a literature review method that analyzed OJK regulations, DSN-MUI fatwas (religious rulings), scholarly journals, and literature on Islamic banking. The findings indicate that NPF risk management in BPRS involves three primary stages: financing feasibility analysis, financing monitoring, and the handling of problematic financing through restructuring, collection, and collateral execution. However, practical implementation faces various challenges, such as the poor quality of financing analysis, limitations in monitoring systems, and the suboptimal application of risk-sharing principles within financing contracts. From the perspective of fiqh muamalah, NPF management must be grounded in the principles of justice (adl), mutual assistance (ta’awun), trustworthiness (amanah), and the prohibition of causing harm (la dharar wa la dhirar). Meanwhile, OJK regulations and DSN-MUI fatwas provide a comprehensive legal framework for financing risk management, although implementation requires further strengthening at the BPRS operational level. This study underscores the importance of integrating Sharia principles with regulatory requirements to bolster financing risk management and support the realization of maqashid sharia (the objectives of Sharia) within BPRS in Indonesia.